Reveal the Antimigraine Mechanism of Chuanxiong Rhizoma and Cyperi Rhizoma Based on the Integrated Analysis of Metabolomics and Network Pharmacology - Zhu, Zhiyao; Wu, Sha; Wang, Yuxuan; Wang, Jiayi; Zhang, Yujia (Frontiers in Pharmacology, 2022)
Migraine is a common neurological disorder that manifests as recurrent attacks of unilateral and throbbing headache. Conioselinum anthriscoides ‘Chuanxiong’ [Apiaceae; Chuanxiong rhizoma] and Cyperus rotundus L. [Cyperaceae; Cyperi rhizoma] (CRCR), is a classic prescription for treating migraine. This study aimed to reveal the potential mechanisms of CRCR extract against migraine using integrated analysis of metabolomics and network pharmacology. Behavioral changes in the nitroglycerin rat migraine model were determined from von Frey withdrawal response. Untargeted serum metabolomics was used to identify the differentially expressed metabolites and metabolic pathways. The differentially expressed metabolites were analyzed to obtain the corresponding targets by a compound-reaction-enzyme-gene network. Network pharmacology was used to construct a compound-target-pathway network. The common targets of metabolomics and network pharmacology were further analyzed. Metabolomics analysis identified 96 differentially expressed metabolites and 77 corresponding targets. Network pharmacology analysis identified 201 potential targets for CRCR against migraine. By intersecting 77 targets with 201 targets, monoamine oxidase A (MAO-A), monoamine oxidase B (MAO-B) and catechol-O-methyltransferase (COMT), were identified as the common targets. And MAO-A, MAO-B and COMT were involved in the tyrosine metabolism pathway. Further experiments demonstrated the contents of MAO-A and COMT were significantly increased in serum and brainstem tissue of the migraine rats. CRCR extract significantly decreased the contents of MAO-A and COMT, while no significant difference was found in MAO-B. Metabolomics analysis indicated the contents of 3,4-dihydroxyphenylacetate (DOPAC) and 3-(4-hydroxyphenyl)pyruvate (HPP) were significantly increased in the migraine rats, and CRCR extract caused significant decreases in DOPAC and HPP. Interestingly, DOPAC and HPP were two differentially expressed metabolites involved in the tyrosine metabolism pathway. Correlation analysis showed DOPAC and HPP were highly positively correlated with MAO-A and COMT. Taken together, 2 key differentially expressed metabolites (DOPAC and HPP), 2 key targets (MAO-A and COMT) and 1 relevant metabolic pathway (tyrosine metabolism) showed great importance in the treatment of migraine. This research could provide a new understanding of the potential mechanism of CRCR against migraine. More attentions should be paid into the tyrosine metabolism pathway in the future study.